Musical Acoustics, Part I, Violin Family Components; Musical Acoustics, Part II, Violin Family Functions - Andrzej RAKOWSKI (Archives of Acoustics)
These two volumes on musical acoustics are devoted to the acoustics of stringed instruments. The editor of both volumes and the author of a part of one book is Carleen M. Hutchins, Permanent Secretary of the Catgut Acoustical Society. This efficient and active Society links both scientists and artists interested in research on musical instruments.